G6PC indicated poor prognosis in cervical cancer and promoted cervical carcinogenesis in vitro and in vivo - Kun Zhu; Chunling Deng; Pan Du; Taorui Liu; Junjie Piao; Yingshi Piao; Meng Yang; Liyan Chen (BMC, 2022)
Abstract Background The glucose-6-phosphatase catalytic subunit (G6PC) is a key enzyme that is involved in gluconeogenesis and glycogen decomposition during glycometabolism. Studies have shown that G6PC is abnormally expressed in various cancers and participates in the proliferation and metastasis of tumors. However, the role of G6PC in cervical cancer remains poorly established. Methods To analyze the expression of G6PC in cervical cancer tissues in patients by immunohistochemistry. Effects of G6PC deregulation on cervical cancer phenotype were determined using MTT, colony formation, transwell, and wound-healing assays. And constructed a nude mouse xenograft tumor model and CAM assay in vivo. The effect of G6PC on glycolysis in cervical cancer was also evaluated. Effect of G6PC on PI3K/AKT/mTOR pathway was detected by Western blot assay. Results In this study, G6PC expression was found to be upregulated in cervical cancer tissues, and this upregulated expression was associated with LN metastasis, clinical stage, recurrence, and disease-free survival and overall survival rates, indicating that G6PC could serve as a novel marker of early diagnosis in cervical cancer. G6PC promoted proliferation, invasion, epithelial mesenchymal transition (EMT) progression, and angiogenesis of cervical cancer cells. Mechanistically, G6PC activated PI3K/AKT/mTOR pathways. The PI3K/AKT pathway inhibitor, LY294002 could partially attenuate the effect. Conclusions G6PC plays a key role in the progression of cervical cancer, and overexpressed G6PC is closely related to patient LN metastasis, clinical stage, recurrence and shortened survival. G6PC promoted cervical cancer proliferation, invasion, migration, EMT progression, and angiogenesis, partially through activating the PI3K/AKT pathway. G6PC, as a metabolic gene, not only plays a role in metabolism, but also participates in the development of cervical cancer. Its complex metabolic and non metabolic effects may be a potential therapeutic target and worthy of further study.